Lumbar paraganglioma. (August 2016) - Dillard-Cannon, Erika; Atsina, Kofi-Buaku; Ghobrial, George; Gnass, Esteban; Curtis, Mark T.; Heller, Joshua
Highlights: Paragangliomas are rare neuroendocrine tumors that present in the spinal cord in only 10% of cases. Superficial siderosis on MRI of an intradural extramedullary spinal tumor should increase suspicion for spinal paraganglioma. Once diagnosed, complete surgical resection is the gold standard therapy, which carries an excellent prognosis. Abstract: Spinal paragangliomas (SP) are benign and overall rare extra-adrenal neuroendocrine tumors often diagnosed during workup for lower back pain. Complete surgical resection achieves both symptomatic relief and cure. We present a 32-year-old man with a longstanding history of lumbago and bilateral lower extremity pain found to have a lumbar paraganglioma at the level of the L3 vertebrae. The clinical, histopathological, and radiological characteristics are described, including the rare finding of superficial siderosis on MRI of the brain. A laminectomy with microscopic dissection of the intradural mass achieved complete debulking without evidence of residual tumor. Excellent prognosis can be achieved with complete surgical resection of SP without the need for adjuvant therapy. Therefore, care should be taken to distinguish these spinal tumors from those that appear similar but are more aggressive. As such, the radiological finding of superficial siderosis should raise the suspicion for SP when a vascular intradural extramedullary spinal tumor is observed.